The effects of a psychiatric clerkship on stigmatizing attitudes toward mental disorders as held by German medical students - Zavorotnyy, Maxim; Klatte, Simon; Yang, Yunbo; Liu, Wei; Wagner, Ulrich; Kircher, Tilo (Frontiers in Psychiatry, 2023)
Background: According to the United Nations, access to medical care is a fundamental human right. However, there is widespread stigmatization of severe mental illnesses, and this appears to seriously hamper the quality of healthcare in people with psychiatric co-morbidity. Thus, interventions that help reduce stigma among healthcare providers are urgently needed. Purpose: The objective of the current study was to investigate the effects of a psychiatric clerkship on stigmatizing attitudes toward mental disorders held by medical students. Methods: Between 2018 and 2019, a total of 256 third- and fourth-year students from Marburg University Medical School (Germany) completed two surveys —one before and one after a two-week clerkship program that was designed to prioritize direct interaction with the patients. For measuring stigma, the questionnaires contained questions about students' attitudes toward psychiatry (ATP) besides the Opening Minds Scale for Healthcare Providers (OMS-HC), Community Attitudes Toward the Mentally Ill (CAMI), and measurements according to the Stereotype-Content Model (SCM). We conducted pre-versus-post comparisons using the Wilcoxon signed rank test with continuity correction or paired t-test and employed the Spearman method for correlational analysis. We considered p-values less than 0.05 significant and adjusted all p-values reported here using the Benjamini-Hochberg procedure to account for family-wise error. Results: After the clerkship, a significantly reduced stigma was found, as assessed with ATP (mean p < 0.001), OMS-HC (sum and subscale "attitudes" p < 0.001; subscale "disclosure" p = 0.002), and both SCM subscales (p < 0.001). Moreover, we observed significant associations between stigma expression (e.g., OMS-HC sum) and the willingness of students to choose psychiatric residency after finishing medical school (before clerkship rho = −0.35, p < 0.001; change after clerkship rho = −0.2, p = 0.004). Conclusion: Our findings indicate that a psychiatric clerkship that involves students in direct interaction with patients may effectively reduce stigma. Therefore, we advocate the incorporation of components of direct interaction in medical education to combat stigma and unequal treatment, as this could improve outcomes in patients with severe mental illnesses.